2017
DOI: 10.7150/thno.18915
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles as Potential Biomarkers for the Identification of Senescence in Human Mesenchymal Stem Cells

Abstract: Senescence in human mesenchymal stem cells (MSCs) not only contributes to organism aging and the development of a variety of diseases but also severely impairs their therapeutic properties as a promising cell therapy. Studies searching for efficient biomarkers that represent cellular senescence have attracted much attention; however, no single marker currently provides an accurate cell-free representation of cellular senescence. Here, we studied characteristics of MSC-derived microvesicles (MSC-MVs) that may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 63 publications
4
81
1
1
Order By: Relevance
“…Recently, EVs produced from cultured MSCs were used to rejuvenate aged hematopoietic stem cells or MSCs . It was reported that young (p2–p6) MSCs produced EVs that could rejuvenate aged murine hematopoietic stem cells in a mouse model , similar to a previous report using MSC‐EVs and an irradiation injury mouse model .…”
Section: Discussionsupporting
confidence: 68%
“…Recently, EVs produced from cultured MSCs were used to rejuvenate aged hematopoietic stem cells or MSCs . It was reported that young (p2–p6) MSCs produced EVs that could rejuvenate aged murine hematopoietic stem cells in a mouse model , similar to a previous report using MSC‐EVs and an irradiation injury mouse model .…”
Section: Discussionsupporting
confidence: 68%
“…miR-720 has been reported to promote odontogenic differentiation and reduce proliferation of dental pulp stem/progenitor cells by repressing Nanog homeobox (NANOG) (10). miR-146a-5p (previously known as miR-146a), a member of the miR-146 miRNA family, has been confirmed to play a significant role in the regulation of stem cell proliferation, differentiation, and apoptosis (11)(12)(13). However, this study is the first to demonstrate that miR-146a-5p is involved in the maintenance of the STRO-1 + DPSC state.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs involved in human‐derived dental stem‐cell maintenance and function have been identified . Recently, it has been reported that miR‐146a‐5p is related to the senescence of human mesenchymal stem cells (hMSCs) and enhances the secretion of vascular endothelial growth factor and the angiogenesis of hMSCs . Overexpression of miR‐146 inhibits the proliferation and promotes the differentiation of mouse neural stem cells .…”
mentioning
confidence: 99%
“…A significant decrease was confirmed for miR-294 and miR-872-3p. In another study, miR-146a and miR-335-5p were up-and down-regulated, respectively, in late passage MSC-EVs versus early passage MSC-EVs but the expression of both miRNAs increased with increasing age in MSC-EVs (Lei et al, 2017). However, the modulated expression of these miRNAs in MSC-EVs was not demonstrated to be related to senescence induction.…”
Section: Characteristics and Function Of Evs From Senescent Or Aged Mscsmentioning
confidence: 93%
“…Increase of EV production is a general feature in aged and senescence-induced cells as shown by several studies as early as 2008 (Lehmann et al, 2008;Beer et al, 2015;Takasugi et al, 2017). Accordingly, the production of EVs by MSCs increases with donor age and late passage cultures (Fafian-Labora et al, 2017Lei et al, 2017). The release of EVs from senescent cells is at least partially dependent on p53 and its downstream target gene tumor suppression-activated pathway 6 (TSAP6).…”
Section: Characteristics and Function Of Evs From Senescent Or Aged Mscsmentioning
confidence: 97%